Emergence of Multi-Drug Resistant Clinical Strains of Staphylococcus aureus - Saha, B; Bal, M (International Journal of Natural Sciences, 2016)
Indiscriminate and wide spread use of antibiotics has lead to the development of multi-drug-resistant strains of pathogenic Staphylococcus aureus. Information regarding increase (in percentage) of existing resistance as well as emergence of new resistance to different antibiotics used for staphylococcal infections are insufficient. This study explores a comparative analysis of growing resistance to different antibiotics mainly ampicillin, methicillin, erythromycin, gentamicin, clindamycin and vancomycin against S. aureus isolated from Kolkata hospitals during two phases. During first phase (126) and second phase (67) non-repeat clinical strains of S. aureus obtained from different hospitals of Kolkata were identified by standard biochemical methods. However, PCR amplification of nuc gene and rDNA was also performed for identification of S. aureus. Antibiotic susceptibility pattern was determined by Disc Agar Diffusion tests and mecA was identified by PCR. Comparative analysis of antibiotic resistance pattern of the strains isolated during two phases showed significant difference (p=0.05) with 75% increase of resistance to erythromycin followed by 30% increase to ampicillin, chloramphenicol and streptomycin with the appearance of vancomycin resistance. Gentamicin and methicillin resistance have increased by 22% and 7% respectively. On the other hand, mecA was obtained by PCR from vancomycin resistant S. aureus strain, which was also resistant to methicillin, erythromycin and clindamycin. This study reveals tremendous increase of resistance to erythromycin and a remarkable increase to other antibiotics with emergence of multidrug- resistant clinical strains of S. aureus. This trend in increasing resistance to the commonly used antibiotics against S. aureus cannot be controlled until and unless antibiotics are used more prudently. International Journal of Natural Sciences (2013), 3(1-4) 1-6